Workshop processes to generate stakeholder consensus about post-mining land uses: an Australian case study. Issue 2 (28th January 2021) - Akbar, Delwar; Rolfe, John; Lechner, Alex M.; Everingham, Jo-Anne; Kinnear, Susan
Abstract : A major challenge in post-mining land use planning is identifying areas of consensus among engaged stakeholders about major concerns and suitable post-mining land use and land management. This paper takes as an example, the Bowen Basin, a major coal-mining region in Australia where several mines are approaching closure stages but consensus on post-mining land use in this region is yet to be established. This paper examines the use of workshop processes to generate consensus among different stakeholder interests about priority issues and acceptable post-mining land use(s) in this region. Four decision-making workshops about post-mining land use were used in this study. Results show that facilitated group workshop processes involving diverse stakeholders could lead to a broad consensus about key options for future land uses at an individual site level; and also lead to the identification of the factors relevant to land-use decisions to be considered for each case study. These findings guide mining companies and government regulators about why and how to involve local and regional stakeholders in post-mining land-use decisions, and the extent to which group processes can lead to convergence of diverse interests.